2010
DOI: 10.1128/ec.00118-10
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role for Exocytosis in Aflatoxin Export in Aspergillus parasiticus

Abstract: Filamentous fungi synthesize bioactive secondary metabolites with major human health and economic impacts. Little is known about the mechanisms that mediate the export of these metabolites to the cell exterior. Aspergillus parasiticus synthesizes aflatoxin, a secondary metabolite that is one of the most potent naturally occurring carcinogens known. We previously demonstrated that aflatoxin is synthesized and compartmentalized in specialized vesicles called aflatoxisomes and that these subcellular organelles al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 18 publications
5
60
0
Order By: Relevance
“…4A yeast extract sucrose (YES) agar medium activates aflatoxin biosynthesis and yeast extract peptone (YEP) agar medium does not activate aflatoxin biosynthesis. It was also established previously that YES and YEP growth media result in differential cellular morphologies -development of unique aflatoxigenic vesicles (aflatoxisomes) in presence of YES but not in YEP (Chanda et al, 2009(Chanda et al, , 2010. We hypothesized that that the accommodation of aflatoxisomes grown in YES would need in a larger hyphal volume that would be reflected in increased average hyphal length and wall strength of the hypha globally across the colony.…”
Section: Comparison Of the Physical Properties Of A Parasiticus Colomentioning
confidence: 88%
“…4A yeast extract sucrose (YES) agar medium activates aflatoxin biosynthesis and yeast extract peptone (YEP) agar medium does not activate aflatoxin biosynthesis. It was also established previously that YES and YEP growth media result in differential cellular morphologies -development of unique aflatoxigenic vesicles (aflatoxisomes) in presence of YES but not in YEP (Chanda et al, 2009(Chanda et al, , 2010. We hypothesized that that the accommodation of aflatoxisomes grown in YES would need in a larger hyphal volume that would be reflected in increased average hyphal length and wall strength of the hypha globally across the colony.…”
Section: Comparison Of the Physical Properties Of A Parasiticus Colomentioning
confidence: 88%
“…In N. crassa, HAM proteins are involved with cell-to-cell fusion or hyphal anastomosis, which is a requirement for asexual and sexual development (43). Several studies have shown that Aspergillus utilizes the endomembrane system for production and transport of the "aflatoxisomes" that function to compartmentalize several of the enzymatic steps leading to production of this toxin (58,59). In the aspergilli, HamI could be required for the correct fusion of vesicles to vacuoles or the plasma membrane to properly synthesize and export secondary metabolites such as NOR and ST.…”
Section: Fig 2 Gene Deletions Of Novel Regulators Inmentioning
confidence: 99%
“…For antifungal activity determination, A. flavus NRRL 3251 mycelia were grown submersed in YES medium (2 % yeast extract and 6 % sucrose, pH 5.8) (12,13), with addition of synthesised compounds (dissolved in DMSO) to obtain the final concentrations of 0, 0.1, 1, and 10 ”g mL ) were prepared according to Ć arkanj et al (10). The final concentration of DMSO in the growth media was 0.1 %.…”
Section: Antifungal and Antiaflatoxigenic Assaymentioning
confidence: 99%